Slam and dc-sign measles receptor polymorphisms and their impact on antibody and cytokine responses to measles vaccine - Clifford, H.; Richmond, P.; Khoo, S.; Zhang, Guicheng; Yerkovich, S.; Le Souëf, P.; Hayden, C. (2011)
Despite the use of measles vaccine, measles virus continues to circulate and cause severe disease. Immune responses to the measles vaccine are variable between individuals, with up to 10% failing to produce a sufficient protective response post-vaccination. Signaling lymphocyte activation molecule (SLAM) and dendritic cell-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN; CD209) are specific measles receptors: SLAM binds and permits entry of the virus into the cell, DC-SIGN acts as an attachment receptor, increasing viral binding efficiency and transmission. Genetic variations in these receptor genes may alter measles vaccine antibody and cellular responses. Methods: In 12-month-old infants from Perth, Western Australia after their first measles vaccine dose as part of the combination measles-mumps-rubella (MMR) vaccine, 7 SLAM and DC-SIGN polymorphisms were genotyped and associations were investigated with measles IgG antibody levels and in vitro measles cytokine responses. Results: The DC-SIGN promoter variant -336C/T was associated with overall IFN-? responses after measles stimulation (P= 0.002) and three DC-SIGN polymorphisms (-336C/T, -139C/T and -871C/T) were associated with the proportion of cytokine non-responders to measles (P= 0.001, P= 0.021 and P= 0.036, respectively). However, no associations were found between the DC-SIGN or SLAM polymorphisms and measles IgG antibody levels. Conclusions: The results suggest that DC-SIGN -139C/T, -336C/T and -871C/T polymorphisms may modulate cytokine (but not antibody) responses to the measles component of MMR vaccine. Furthermore, contrasting previous studies, SLAM polymorphisms do not appear to affect measles antibody or cytokine responses in this cohort. © 2011.